The influence of growing factors on the productivity indicators of soybean [Glycine max (L.) Merrill] - О. В. Топчій; Л. М. Присяжнюк; А. П. Іваницька; Н. П. Щербиніна; З. Б. Києнко (Plant Varieties Studying and Protection)
Purpose. To determine the patterns of influence of growing factors on the economically valuable characteristics of new soybean varieties. Methods. Field, biochemical methods, analysis of variance. Results. The rates of the influence of the growing zone, the conditions of the growing season of the year and the soybean variety on the yield, weight of 1000 seeds, the content of crude protein and oil, and protein and oil collection were determined. The greatest influence on the yield of the studied varieties had a growing zone – 55%. On average the maximum yield was obtained in Forest-steppe zone 2.48–3.58 t/ha, the lowest – in Steppe zone (1.33–1.89 t/ha) for 2017–2018. In the same period the weight of 1000 seeds on average was 125.1–169.9 g in the Steppe zone, in Forest-Steppe zone it was 130.2–207.8 g and 143.9–188.0 g in Forrest zone. According to the results of analysis of variance, it was determined that the growing zone has the greatest influence on weight of 1000 seeds – 31%, variety – 21% and conditions of the growing season of the year – 13%. The main characteristics of soybean quality are the content of crude protein and oil in seeds. The highest level of crude protein was observed in soybean variety in Forest-Steppe zone – 37.5–44.0%. In Forrest zone, the crude protein content was 34.4–41.7%, in the Steppe zone 35.4–40.1%. The maximum level of this characteristic was observed in variety ‘NS Diyana’ – 44.0% in Forest-Steppe zone, in Forrest zone – in the variety ‘Alexa’ 41.7%, in Steppe zone – in variety ‘NS Diyana’ 40.1%. Thus, the growing zone (31%) and variety (25%) had the greatest influence on the content of crude protein; the interaction of factors (variety and growing zone) affected 17%. The average oil content for 2017‑2018 ranges from 19.8 to 24.2%. High oil content was noted in ‘Adsoy’ variety in Forrest and Forest-Steppe zones, 24.2 and 22.6%, respectively, and ‘Azimut’ – 23.8% in Steppe zone. The results of the analysis of variance showed that the growing zone to a greater extent affected the oil content in soybean seeds by 25%, variety – 21%, and the interaction of factors of the variety and growing zone by 21%. Conclusions. According to the results of multifactor analysis of variance, it was determined that the growing zone had the greatest influence on the studied parameters. It was found that the rate of the influence of growing zone of soybean varieties is 25–55%, depending on the studied characteristic. It was determined that the influence of the variety was 4–25%, the conditions of the growing season affected by 1–26%.